2016
DOI: 10.1016/j.bbrep.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt ions recruit inflammatory cells in vitro through human Toll-like receptor 4

Abstract: Metal-on-metal (MoM) hip replacements, often manufactured from a cobalt-chrome alloy, are associated with adverse reactions including soft tissue necrosis and osteolysis. Histopathological analysis of MoM peri-implant tissues reveals an inflammatory cell infiltrate that includes macrophages, monocytes and neutrophils.Toll-like receptor 4 (TLR4) is an innate immune receptor activated by bacterial lipopolysaccharide. Recent studies have demonstrated that cobalt ions from metal-on-metal joints also activate human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
10
1
1
Order By: Relevance
“…Although in vitro detection of many inflammatory mediators was not significantly altered by either hypoxia or LPS stimulation in neutrophils (231), others have shown an increase in IL-8 gene and protein expression in CoCl 2 -induced hypoxia conditions in human endothelial cells (232). In contrast to our results, it has been reported that CoCl 2 increases the release of inflammatory cytokines through TLR4 pathways in immune cells like monocytes and neutrophils (233,234).…”
Section: Hypoxia and Effects On Pro-inflammatory Gene Expression And Cs Insensitivitycontrasting
confidence: 99%
“…Although in vitro detection of many inflammatory mediators was not significantly altered by either hypoxia or LPS stimulation in neutrophils (231), others have shown an increase in IL-8 gene and protein expression in CoCl 2 -induced hypoxia conditions in human endothelial cells (232). In contrast to our results, it has been reported that CoCl 2 increases the release of inflammatory cytokines through TLR4 pathways in immune cells like monocytes and neutrophils (233,234).…”
Section: Hypoxia and Effects On Pro-inflammatory Gene Expression And Cs Insensitivitycontrasting
confidence: 99%
“…This is also supported by TLR4 and IL6/IL8 results of Cr(3+) and Ni(2+) exposed cells. Lawrence and co-workers already showed, that Co(2+) activates TLR 4 which is in turn associated with enhanced chemokine release [39,40]. In contrast, Samelko et al (2016) reported that CoCr particles did not preferentially activate TLR4 induced inflammation [41].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of cobalt to induce apoptotic signaling was also demonstrated (Akbar et al, 2011). In line with induction of oxidative stress, cobalt was also capable of stimulation of proinflammatory milieu through proinflammatory cytokine overproduction, migration of immunocompetent cells via activation of Toll-like receptors 4 (TLR4) (Lawrence et al, 2016). Although cobalt-induced activation of HIF-1, being redox-and metal-sensitive transcription factor is considered as the key mechanism of physiological effect of cobalt, this process may also mediate certain toxic effects of cobalt exposure (Maxwell and Salnikow, 2004).…”
Section: Toxicitymentioning
confidence: 96%